2003
DOI: 10.1111/j.1744-7348.2003.tb00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Water relations and leaf gas exchange properties in some elite canola (Brassica napus) lines under salt stress

Abstract: In order to examine whether growth of eight genetically diverse canola (Brassica napus) lines under salt stress is positively associated with their rate of photosynthesis and other gas exchange related attributes, 20-day old plants of all eight lines were subjected to salinised soil containing 2.4 dS m -1 NaCl (control), 4 dS m -1 NaCl, 8 dS m -1 NaCl or 12 dS m -1 NaCl. The lines DGL (non canola) and Dunkeld were found to be salt tolerant and Rainbow and Cyclon salt sensitive with regard to shoot dry matter p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Accumulation of solutes especially proline, glycine-betaine and sugars is a common observation under stress condition (Qasim et al, 2003). Ashraf et al (1990) revealed that proline is an important osmolyte to adjust the plant under drought/saline conditions.…”
Section: Effects Of Salinity On Antioxidative Enzymes and Antioxidantsmentioning
confidence: 99%
“…Accumulation of solutes especially proline, glycine-betaine and sugars is a common observation under stress condition (Qasim et al, 2003). Ashraf et al (1990) revealed that proline is an important osmolyte to adjust the plant under drought/saline conditions.…”
Section: Effects Of Salinity On Antioxidative Enzymes and Antioxidantsmentioning
confidence: 99%
“…Proline acts as antioxidant and scavenged reactive oxygen species (ROS). Proline, glycine betaine and sugars were solutes, accumulated in plant parts under stressed condition (Qasim et al, 2003). Proline concentration varies from 5% under normal condition to 80% under stressed condition in many plants (Szabados and Savoure, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Salt injury of plant leaves and stems is resultant of maximum inflow of Classociated with drop of K + uptake (Sharma, 1995). Accumulation of solutes especially proline, glycine-betaine and sugars is a common observation under stress condition (Qasim et al, 2003). Leaf proline content in salt stressed plants increased as observed in maize by Carpici et al (2010) and Moussa (2006).…”
mentioning
confidence: 80%